Antiparasitic effect of biogenic iron nanoparticles against the fish ectoparasite Argulus siamensis: In vitro study: Antiparasitic effect of iron nanoparticles against Argulus - Brahmchari, R. K.; Kumari, Pushpa; Kumar, Saurav; Sharma, Rupam; K. Pani Prasad; Srivastava, P. P.; Raman, R. P. (Indian Journal of Fisheries, 2023)
Argulus, an ectoparasite of fish which is ubiquitous in wild and culture ponds, poses a majorchallenge with severe economic losses to the global aquaculture industry. With the increasein intensification of aquaculture practices, there is a dire need to discover new therapeuticoptions in the treatment of argulosis owing to the limited effectiveness of existing drugsand chemicals and their significant side effects. The use of metal nanoparticles hasshown promising results in the management of several parasitic infections. In this prelude,antiparasitic effect of biosynthesised iron nanoparticles was evaluated against Argulussiamensis under in vitro condition. Iron nanoparticles (FeNPs) were biosynthesised usingfresh Bauhinia racemosa leaf extract as a reducing agent and were characterised usingUV-VIS spectrophotometry, dynamic light scattering (DLS) technique, zeta potentialmeasurements, transmission electron microscopy (TEM), scanning electron microscopy(SEM), and fourier transform-infrared spectroscopy (FT-IR). For estimating antiparasiticefficacy of FeNPs under in vitro test, ten adult and juvenile parasites each were challengedfor 6 h separately in 20 ml of five different concentrations of FeNPs test solutions viz. 1.00,1.25, 1.50, 1.75 and 2.00 mg ml-1 in triplicate along with control groups for adults whereas,for juveniles, it was 0.75, 1.00, 1.25, 1.50 and 1.75 mg ml-1. Formation of FeNPs wasmeasured in 370-400 nm UV range. DLS showed an average FeNPs particle size of 119.8 nmwith a polydispersity index of 0.311. Zeta potential measurements showed negative surfacecharges (-11.3 mV) whereas, SEM and TEM micrographs revealed synthesised nanoparticleswere nearly spherical and size ranged from 60-270 nm. Further, FT-IR spectrum showed thepresence of Fe-O, N=O and O-H groups. Argulocidal effectiveness in both cases was foundto be concentration-dependent. The highest argulocidal activity of FeNPs was observed atconcentration of 1.75 mg ml-1 for juveniles and 2.00 mg ml-1 for adult argulids which led to100 and 87% mortality, respectively, in 6 h, however no mortality was recorded in controlgroup up to 16 h. Furthermore, the calculated 6 h-EC50 of biosynthesised FeNPs for juvenileand adult argulid parasites was determined as 0.97 and 1.27 mg ml-1. Results of the presentstudy showed that short term bath treatment with biosynthesised FeNPs is effective againstargulid parasites. However, further research is required to evaluate its therapeutic potentialunder in vivo condition.Keywords:Argulosis, Argulus siamensis, Iron nanoparticles,Parasiticidal activity